I was better last night : a memoir - Fierstein, Harvey, 1952- (Alfred A. Knopf, 2022)
"A revealing, poignant, and hilarious memoir from the cultural icon, gay rights activist, and four-time Tony Award winner. Harvey Fierstein's stellar career has taken him from Broadway to Hollywood and back. He's received accolades and awards for acting-Hairspray, Fiddler, Mrs. Doubtfire, Independence Day-and writing: La Cage Aux Folles, Torch Song Trilogy (for which he also won a Tony for acting) and Kinky Boots. But while he is widely known as one of today's most peerless performers, Harvey has never shared his own story until now"--